We can start simplifying the boolean expression by using the absorption law, which states that a variable ANDed with its complement is equivalent to 0.
Using this law, we know that a'bc + a'c' = a'c'.
So, f = a'c' + b'c.
Next, we can use the distributive law, which states that a variable ORed with the product of two other variables is equivalent to the sum of the variable ORed with each of the individual variables.
Using this law, we can simplify f further:
f = a'c' + b'c
= a'c' + b'cc'
= a'c' + b'c(c'+c)
= a'c' + b'cc' + b'c
= a'c' + 0 + b'c
= a'c' + b'c
This is the minimum form of the boolean expression, with only two literals.